Polyostotic fibrous dysplasia of the craniofacial bones: a case report - Haryono, Derry; Priaminiarti, Menik; Wijanarko, Aloysius Putut; Saraswati, Inka; Ananda, Nissia (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2026)
Objectives: This case report is aimed to show the radiographic features of fibrous dysplasia, a rare benign condition of abnormal bone growth that progresses slowly and is marked by uneven bone trabeculae interspersed with excessive proliferation of cellular fibrous connective tissue. Case Report: An 18-year-old female patient with a chief complaint of swelling on the right upper cheek was referred to the Oral and Maxillofacial Department of Universitas Indonesia Hospital. The patient is then referred to the Radiology Department to undergo a panoramic and CT scan examination. On panoramic and CT examination, signs typical of polyostotic fibrous dysplasia were found, namely “ground glass appearance” with ill-defined borders, which extended unilaterally and extended from the maxilla and mandible to the frontal bone. Conclusion: Polyostotic fibrous dysplasia can be identified on panoramic radiographs, a reliable and widely available diagnostic tool. Computed tomography (CT) is an advanced imaging modality for further evaluation of the lesion extension and tissue involvement. Management requires careful consideration of multiple clinical and radiographic factors.